Three-Dimensional Manipulation for Self-Focusing Behavior via the State of Polarization - Lu, Lu; Wang, Zhiqiang; Lin, Rong; Cai, Yangjian (Frontiers in Physics, 2022)
In this work, the controllable self-focusing behavior by manipulating the state of polarization (SoP), i.e., phase difference between two orthogonal polarized components at the initial optical field, is firstly investigated, which can be used to realize the three-dimensional manipulation of self-focusing behavior. Furthermore, the properties of self-focusing propagation (including intensity distribution, propagation dynamics and Stokes parameters) are researched in detail, which is beneficial to select the reasonable initial SoP for the further theoretical and experimental exploration. Particularly, the radially-polarized beam as a laser source not only prolongs the self-focusing length but also improves the power density of self-focusing spots on the target. These findings may have potential in the multi-dimensional optical manipulation, the optical information transmission, the high-power long-range laser atmospheric propagation, and related applications.